Hábeas corpus y derechos de los animales. - Orbe García, Génessis Mikaela (2023)
The purpose of this document is to study and analyze the judgment issued by the Constitutional Court of Ecuador, Number 253-20-JH/22, in order to detail and specify the actions of the judges. In addition, in order to understand the new legal currents that have developed in favor of animal law, contrasting this information with the history and particularities of habeas corpus, as well as the legal reality of the same figure; detailing what are the changes that it has gone through and according to what situations it has been modified over time. For this, the analytical historical method allows us to infer some situations that the world of law went through to become what it is today and to be able to guarantee people's right to freedom, after that; later, thanks to social struggles we allow ourselves to raise the question of whether it is possible to adapt the jurisdictional guarantees applicable to humans for the benefit of animal rights, especially those in captivity. In the same way, the hermeneutic and analytical method has been useful when studying several international cases; which have been important, because they have made it possible to establish the need for change in the legislation of each country, in order to guarantee animal rights, especially, when it comes to their freedom affected by a captivity that not only threatens the species but the integrity of each specific species. Finally, a legal-critical study of the aforementioned case has been prepared to propose currents and different actions in the future, when similar cases arise related to the legal problem that I address in this degree work.